Phenanthrenes from Juncus effusus - Su, Xue-Hui; Yuan, Zhi-Peng; Li, Cong-Ying; Zhong, Yu-Jiao; Du, Hong-Jian; Wen, Ya-Ya; Li, Yan-Fang; Liang, Bing (Planta Medica, 2013)
A chemical investigation of the EtOAc-soluble fraction from the ethanol extract of the medullae of Juncus effusus led to the isolation of three new 9,10-dihydrophenanthrenes, juncuenins E–G (1–3); two new phenanthrenes, dehydrojuncuenins D–E (4–5); one new feruloylated glycoside (6); and one known 9,10-dihydrophenanthrene (7). The structures of these compounds were determined by analyzing their spectroscopic data. Metabolites 1–4 and 7 were further evaluated for their in vitro cytotoxic activities against seven human cancer lines (A549, MCF-7, BEL-7402, HeLa, COLO205, BGC-823, and SK-OV-3). Among them, compound 1 exhibited weak cytotoxicity against MCF-7 and HeLa cell lines. Compound 7 showed moderate cytotoxicity against MCF-7 and HeLa cell lines, with IC50 values of 9.17 and 19.6 µM, respectively.
Keywords: Juncus effusus; Juncaceae; phenanthrenes; feruloylated glycoside; cytotoxic activities